10H-Indolo[3,2-b]quinoline, a Potent Brine Shrimp Toxin from Justicia betonica - ARUNAKUMARI, ANDY; V. RAMANI, MODUKURI; V. SUBBARAJU, GOTTUMUKKALA (Asian Journal of Chemistry, 2012)
10H-Indolo[3,2-b]quinoline, an alkaloid from Justicia betonica, exhibited a very potent brine shrimp lethality, but no significant anti-oxidative or 5-lipoxygenase inhibitory activities.